AB0072 A MULTICOMPONENT MEDICATION PROMOTES CHONDROGENESIS AND REDUCES MMP-13 IN PRIMARY ARTICULAR CHONDROCYTES FROM KNEE OSTEOARTHRITIS PATIENTS IN VITRO. (2nd June 2020) - Sanchez, C.; Hemmer, K.; Kroemmelbein, N.; Seilheimer, B.; Dubuc, J. E.; Antoine, C.; Henrotin, Y.
Abstract : Background: HE-1100 is a multicomponent medicinal product. Initial preclinical data potentially suggest a preventive effect on cartilage degradation. Objectives: This study aims to understand the mode of action of HE-1100 on OA chondrocytes in vitro . Methods: Primary chondrocytes were obtained from 10 knee osteoarthritis (OA) patients undergoing knee replacement surgery. The cultures were treated with 20% (v/v) HE-1100 or placebo. Samples were collected for subsequent RNA extraction using standard methods. The reads were generated with Illumina NextSeq5000 sequencer and aligned to the human reference genome (UCSC hg19) to generate the transcriptome. Differential expression analysis between HE-1100 and placebo was made in R using the DESeq2 package to identify the differentially expressed genes in the OA-associated regulatory pathways. The protein production of the selected genes was quantified by ELISA in 10 independent human OA chondrocytes cultures. Results: According to the DESeq2 analysis, HE-1100 significantly modified the expression of 13 genes in OA chondrocytes by at least 10% with an adjusted p-value < 0.05: EGR1 (+93%), FOS (+87%), NR4A1 (+43%), DUSP1 (+18%), ZFP36 (+18%), ZFP36L1 (+14%), NFKBIZ (+16%) and CYR61 (+14%) were upregulated and ATF7IP (-10%), TXNIP (-11%), C10orf10 (-12%), CLEC3A (-12%) and MMP13 (-18%) were downregulated after 24h HE-1100 treatment. HE-1100 significantly increased (2.3 fold +/-1.2 after 24h, p=0.0444 and 2.3-fold +/-1.0 after 72h, p=0.0239) the CYR61 protein production by human OA chondrocytes. After 72h, HE-1100 slightly but not significantly increased aggrecan production by 14 ± 19 % (p=0.1117) and significantly increased type II collagen pro-peptide production by 27 ± 20 % (p=0.0147). For both time points CYR61 production by OA chondrocytes was positively and significantly correlated with aggrecan (r=0.66, p=0.0004) and type II collagen pro-peptide (r=0.64, p=0.0008) production. In alginate beads culture, pro-MMP-13 was significantly decreased by HE-1100 treated cultures from day 7 to day 14 (from -16 to -25 %, p<0.05) and from day 17 to 21 (-22 %, p=0.0331) in comparison to controls. Conclusion: HE-1100 significantly modified the expression of DUSP1, C10orf10, ZFP36/L1 and CLEC3A, which are pathway mediators involved in MMP-13 expression and activation. Further, long-term (28 days) treatment with HE-1100 significantly reduced the production of pro-MMP-13, the inactive precursor of the metalloproteinase MMP-13 involved in type II collagen degradation. HE-1100 also promoted extracellular matrix formation probably through CYR61 production, a growth factor well correlated with type II collagen and aggrecan production. References: / Acknowledgments: We would like to thank the staff of the GIGA ULiège Genomic Next Generation Sequencing platform for performing the RNA sequencing and Benoit Charloteaux for his help in RNAseq data analysis. Disclosure of Interests: christelle sanchez: None declared, Kathrin Hemmer Employee of: Heel, Natascha Kroemmelbein Employee of: Heel, Bernd Seilheimer Employee of: Heel, Jean-Emile Dubuc: None declared, Christophe Antoine Employee of: Artialis, Yves Henrotin Grant/research support from: HEEL, TILMAN